Safety and efficacy of agomelatine in children and adolescents with major depressive disorder receiving psychosocial counselling: a double-blind, randomised, controlled, phase 3 trial in nine countries. (February 2022) - Arango, Celso; Buitelaar, Jan K; Fegert, Jörg M; Olivier, Valérie; Pénélaud, Pierre-François; Marx, Ute; Chimits, Damien; Falissard, Bruno; ,; Barylnik, Julia; Birdeanu, Laura; Bosch, Gert P; et al.
Summary: Background: Major depressive disorder is a severe illness that frequently manifests before the age of 18 years, often recurring later in life. Paediatric medical treatment options are scarce. The melatonin receptor agonist and 5-hydroxytryptamine2C receptor antagonist agomelatine is used to treat adults, and could offer a new therapeutic option for paediatric patients. Therefore, we aimed to investigate the short-term antidepressant efficacy and safety of agomelatine in children and adolescents with major depressive disorder. Methods: We performed a 12 week, randomised, double-blind, parallel-group, multicentre, phase 3 trial in 46 specialist psychiatric units or centres in Bulgaria, Finland, Hungary, Poland, Romania, Russia, Serbia, South Africa, and Ukraine. Participants (aged 7–17 years) were eligible if they were unresponsive to psychosocial therapy during the 3-week run-in period (Children's Depression Rating Scale–revised [CDRS-R] score of ≥45). Ethnicity was not recorded. We investigated short-term antidepressant efficacy of agomelatine (10 mg or 25 mg per day) versus placebo with an active control (fluoxetine 10–20 mg depending on symptom severity) after 12 weeks of treatment in children (aged 7–11 years) and adolescents (12–17 years) with major depressive disorder. Patients were randomly assigned (1:1:1:1) to agomelatine 10 mg, agomelatine 25 mg, placebo, or fluoxetine via an interactive response system with permuted-block randomisation. Standardised manualised psychosocial counselling, developed for this trial, was initiated from selection and continued throughout the study, including the open-label extension. All people involved in the conduct of the clinical trial and patients were masked to treatment allocation. Study outcomes were measured using standardised interviews at each study visit. The primary endpoint was change in CDRS-R raw score from baseline to week 12. This study is registered with EudraCT, 2015-002181-23. Findings: Between Feb 23, 2016, and Jan 14, 2020, 466 individuals were assessed for eligibility and of 400 included patients, 396 (247 [62%] girls, 149 [38%] boys; mean age 13·7 years [SD 2·7]) were analysed (full analysis set). The primary objective was met; 25 mg/day agomelatine (n=94, with n=102 receiving 10 mg/day) resulted in an improvement versus placebo (n=101) in CDRS-R raw score of 4·22 (95% CI 0·63–7·82; p=0·040) at 12 weeks, with a similar effect for fluoxetine (n=99), establishing assay sensitivity. The overall effect was confirmed in adolescents (n=317), but not in children (n=79). No unexpected safety signals were observed with agomelatine, with no significant weight gain or effect on suicidal behaviours. Interpretation: This first study in a paediatric population supports the efficacy of 25 mg/day agomelatine, in addition to psychosocial counselling, in treating adolescent patients with major depressive disorder, with no unexpected safety signals. This medication could provide another option in the limited psychopharmaceutical repertoire for management of major depressive disorder. Funding: Servier. Video Abstract: Prof Bruno Falissard introduces the paper on the safety and efficacy of agomelatine in combination with psychosocial counselling in children and adolescents with major depressive disorder. Youtube URL: https://youtu.be/5SB_2YZAY-0